2009
DOI: 10.5694/j.1326-5377.2009.tb02626.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining communication and team performance during clinical handover in a complex environment: the private sector post‐anaesthetic care unit

Abstract: Threats to patient safety during clinical handover have been identified as an ongoing problem in health care delivery. In complex handover situations, organisational, cultural, behavioural and environmental factors associated with team performance can affect patient safety by undermining the stability of team functioning and the effectiveness of interprofessional communication. We present a practical framework for promoting systematic, comprehensive measurement of the factors involved in clinical handover. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…The idea of context‐specific mnemonics has considerable benefit where SBAR is used where the patient is deteriorating or emergency departments where unstable conditions exist for patients. Others have suggested that competing initiatives could result in ‘reform fatigue’ . Similarly, Botti argued that the ‘uptake of clinical handover tools has been low’, suggesting that there is limited ecological validity or ‘the degree to which interpretations or innovations reflect the real‐life situations in which they are to be applied’ (p. S159) .…”
Section: Discussionmentioning
confidence: 99%
“…The idea of context‐specific mnemonics has considerable benefit where SBAR is used where the patient is deteriorating or emergency departments where unstable conditions exist for patients. Others have suggested that competing initiatives could result in ‘reform fatigue’ . Similarly, Botti argued that the ‘uptake of clinical handover tools has been low’, suggesting that there is limited ecological validity or ‘the degree to which interpretations or innovations reflect the real‐life situations in which they are to be applied’ (p. S159) .…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of health care means that maintaining the continuity of patient care is a challenging process. As the article by https://doi.org/10.5694/j.1326-5377.2009.tb02626.x on maximising patient safety in complex handover situations states, “it is unlikely that any one improvement strategy will be appropriate for all” 16 . Training in communication within a team seems to be a helpful strategy, as demonstrated by https://doi.org/10.5694/j.1326-5377.2009.tb02619.x in a study of TeamSTEPPS (team strategies and tools to enhance performance and patient safety) 17 .…”
Section: The Effects Of Health Care Culture and Organisational Structurementioning
confidence: 99%
“…The methods, adapted from quality improvement (Ben‐Tovim et al., ; Calder et al., ), used a novel patient mapping approach and data collection guided by tools developed for PACU handover improvement (Agarwal et al., ; Botti et al, ; Redley et al ) to explore the impact of handover communication in complex clinical environments. Integration of description using quantitative and qualitative data offered robust data and the opportunity to explore the detail of care delivery in the PACU.…”
Section: Discussionmentioning
confidence: 99%
“…The anaesthetist to nurse handover was observed for compliance with elements of the Connect, Observe, Listen, Delegate (COLD) quality improvement tool developed previously by one of the researchers (Botti et al, ; Redley et al ). The Listen step of this process included the elements of Identify, Situation, Observations, Background, Assessment and Recommendation (ISoBAR) (Porteous, Stewart‐Wynne, Connolly, & Crommelin, ; Yee, Wong, & Turner, ) recommended to standardise the verbal communication during PACU handover (Agarwal et al., ; Botti et al, ; Redley et al ).…”
Section: Methodsmentioning
confidence: 99%